Treatment of Bullous Systemic Lupus Erythematosus - Lihua Duan; Liying Chen; Shan Zhong; Ying Wang; Yan Huang; Yan He; Jie Chen; Guixiu Shi (Journal of Immunology Research)
Bullous systemic lupus erythematosus (BSLE) is an autoantibody-mediated vesiculobullous disease in patients with SLE. Autoimmunity in BSLE is characterized by the presence of circulating anti-type VII collagen antibodies. BSLE patients often present with multiple, tense, clear fluid-filled vesicles and bullae overlying erythematous edematous plaques. Skin biopsy from BSLE patients shows subepidermal bullae with numerous neutrophils and only occasional eosinophils. Furthermore, immunofluorescence examination showed linear deposition of lgG, lgA, C3, and C1q along the basement membrane zone. BSLE patients with corticosteroids treatment constantly do not receive a marked improvement, while dapsone generally dramatically improved the skin condition. Recently, it has been reported that quite a few cases of BSLE were successfully treated with other immune suppressive drugs. Therefore, a comprehensive review of the treatment of BSLE would be beneficial to cure the disease.